Penguatan Kemampuan Siswa Binaan Yayasan Zayna Nurfirdaus (Yazani) Melalui Pengajaran Matematika, Bahasa Inggris, dan Komputer Dasar - Khumairoh, Alvi; Prasanti, Fanya Jessica; Zamaya, Raihani Mufti; Widyastuti, Hardiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Improving the quality of education in Indonesia is an essential step toward achieving Sustainable Development Goal (SDG) 4: Quality Education. This study aims to describe the implementation of a community service-based teaching program conducted in collaboration with the Zayna Nurfirdaus Indonesia Foundation (Yazani). The program focused on enhancing students’ competencies in Mathematics, English, and Basic Computer Skills. The teaching approach was interactive and participatory, incorporating visual media, educational games, small group discussions, and formative assessments through pre-tests and post-tests. Teaching strategies were adapted to meet students’ needs, including the use of coaching cards to guide independent learning, project-based activities (such as designing name cards or simple digital posters), and hands-on simulations for computer-based lessons. Activities were designed to encourage active learning, collaboration, and increased student confidence in completing academic tasks. The program was carried out over three months (September–November 2024), involving students supported by the foundation. Evaluation results indicated significant academic improvements: average Mathematics scores increased by 60%, English scores rose from 48 to 92, and Basic Computer Skills improved by 71.7%. Additionally, observations and interviews revealed greater student motivation and engagement throughout the learning process. These findings suggest that university student involvement through adaptive, student-centered teaching methods can contribute positively to improving educational outcomes. This program demonstrates a collaborative model that supports inclusive and sustainable education at the elementary level.